A Standard Content for University Websites Using Heuristic Evaluation - Jainari M.H.; Baharum A.; Deris F.D.; Mat Noor N.A.; Ismail R.; Mat Zain N.H. (Springer Science and Business Media Deutschland GmbH, 2023)
With the rapid development of the internet, a growing number of educational websites, and the high demanding usage of the Word Wide Web (WWW) as an information-seeking platform, the importance of e-learning has also increased. Additionally, as more complex information is included in the university website, it also has become difficult to look for needed information. The need to look into university website usability and standard content are crucial to fully ensure the website function. This study aims to identify a standard university website content using heuristic evaluation. The strategies start from a review of the studies on standard university website contents and benchmarking against other universities. Then, a prototype of the university website will develop using the standard content obtained and finally evaluated on the usability. The results show that the About Us, Admission, and Contact Us section was identified as a standard and best practice for university website content. This study will help in designing standard website content for the University. 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.